Redefining critical capabilities for business performance of Malaysian Manufacturing SMES / Noraini Ismail ... [et al.] - Ismail, Noraini; Amir Ishak, Noormala; Abdul Karim, Norminsham; Ismail, Norlia (UPENA, 2010)
There are many factors plaguing the performance of small businesses in general. However, not many studies have been done to ascertain particular capability as important and significant in influencing the business performance of a particular industry. Both qualitative and quantitative research approaches were used in the study. The former was undertaken via focus group interview to solicit new information as well as unravel other factors deemed necessary for business success. The outcome of this focus group analysis led to the development of the research framework and the research instrument. Data were gathered from 290 SMEs through a proportionate sampling design from the 6 top industries representing the manufacturing sector via a nationwide survey. Descriptive and regression analyses were run to ascertain and examine relationships amongst variables. SMEs reportedly admitted to the need for innovation capabilities to drive business performance. Furthermore, both quality system and technical capabilities were more prevalent for Journal of International Business and Entrepreneurship manufacturing SMEs in influencing business success compared to other capabilities like finance and management that hold true historically. This study has provided evidence for manufacturing entrepreneurs to migrate from financial dependence to innovation dependence for business success. The findings may provide a new research avenue like defining innovative characteristics/ competencies required of SMEs as a driver for success. On policy implication, the government may want to develop niche innovation strategies for small businesses instead of relying on the "one strategy fits all businesses" policy.